Persistence and geochemical differentiation of drilling waste in unconsolidated deep-sea sediments from the Ulleung Basin, East Sea - Jong-Hwa Chun; In Kwon Um; Yong Hoon Kim (Marine Pollution Bulletin, 2026)

DAPL1 is activated by Np63 and GRα and regulates lipid metabolism - Heung-Seok Bae; Yong-In Kim; DongWook Kim; Ki-Hoan Nam; KyungSook Han; SunJo Kim; SungWon Kwon; Je-Yoel Cho (Journal of Molecular Medicine, 2026)
Non-small cell lung cancer (NSCLC) accounts for about 80% of all lung cancer occurrences and is divided into largely Adenocarcinoma (LUAD), Squamous cell carcinoma (LUSC), and Large cell carcinoma. In this study, using RNA-seq data between cancer tissues and adjacent normal tissues of 5 LUAD and 4 LUSC patients, we found that a Death associated protein like 1 (DAPL1) was highly expressed in squamous cell carcinoma but not in adenocarcinoma. Through the RNA-seq analysis, we found that lipid metabolic pathway genes Fdft1, Pcyt1a, and Sptlc1 correlate well with DAPL1 level changes in LUSC. We also found that Dapl1 was activated by Np63 and GRα monomer transcription factors. We generated a DAPL1 knockout mouse, which shows body weight and hair color changes, implying the role of DAPL1 in lipid metabolism. Our data show that Np63, GRα transcription factors activate DAPL1, and it is predicted to contribute to cellular acidification by regulating lipid metabolism based on mRNA-seq data and DAPL1 KO mice. Key messages This study uses RNA-seq data between cancer tissues and adjacent normal tissues of 5LUAD and 4LUSC patients. We found that a Death associated protein like 1 (DAPL1) was highly expressed in squamous cell carcinoma but not in adenocarcinoma. We also found that Dapl1 was activated by Np63 and GRα monomer transcription factors. The RNA-seq analysis found that lipid metabolic pathway genes Fdft1, Pcyt1a, and Sptlc1 correlate well with DAPL1 level changes in LUSC. We generated a DAPL1 knockout mice. DAPL1 KO mice were bred at two institutions (KRIBB for phonotypes, and SNU for functions). Interestingly, in KRIBB, DAPL1 KO body weight was lower than WT, and in SNU, DAPL1 KO body weight was higher than WT. In the investigation of mouse chow from the two institutions, differences in choline were noted. When chow with differences only in choline was produced and applied to new DAPL1 KO mice, the same results were obtained. Through RNA-seq data and body weight changes in DAPL1 KO mice, we report that DAPL1 regulates cholesterol, PC, and SM through changes in mRNA of Fdft1, Pcyt1a, and Sptlc1. Our data show that Np63, GRα monomer transcription factors activate DAPL1, and it is predicted to regulate lipid metabolism based on mRNA-seq data and DAPL1 KO mice.

A new integrated process from non-edible biomass to 2,5-furandicarboxylic acid via 5-bromomethylfurfural and 5-acetoxymethylfurfural intermediates - In Yong Eom; Jihoon Kim; Jiyun Yoo; Gihyun Kwon; Maeum Lee; Faraz Muhammad Abbasi; Bolla Srinivasa Rao; Heedo Ryou; Jeehoon Han; Dong Won Hwang (Chemical Engineering Journal, 2026)

Multiscale characterization and effective elastic properties of avery island rock salt - In Kyu Jeon; Yong-Rak Kim; Kyung Won Chang (Geomechanics for Energy and the Environment, 2026)

Allergenicity of edible insect proteins: Cross-reactivity, processing effects, and food safety considerations - Jae Hoon Lee; Ji Yoon Cha; Seonmin Lee; Yea-Ji Kim; Jeong-Heon Kim; Dong Hyun Keum; Hae In Yong; Min Hyeock Lee; Yun-Sang Choi (Food Chemistry, 2026)

Metabarcoding detection of Vibrio species in black-tailed gulls reveals seabirds as overlooked sentinels of coastal zoonotic risk in South Korea - Singeun Oh; Dewi Arinta; Buyanbadrakh Burenbaatar; Jun Ho Choi; Leon Kim; Du-Yeol Choi; Dongjun Kang; Arwa Shatta; Myung-hee Yi; Yoon Hee Cho; In-Yong Lee; Ju Yeong Kim (Environmental Research, 2026)

Probabilistic risk assessment of dietary exposure to acrylamide in Korean adolescents (12–18 years) based on KNHANES 2017–2023 data - Yong-Sik Yoon; Young-Soo Kim; Eun-In Yang; Soon-Il Yun; Sooah Kim (Food Additives & Contaminants: Part A, 2026)

Hydrogen production via direct core-shell conjugation of functionalized fullerenes and ZnO QDs with accelerated optical catalytic properties - Juhee You; Dan Na; Yuwen Wei; Hyunjin Cho; Seok-Ho Seo; Young Jae Park; Dong Gwon Heo; Sang-Youp Yim; Seunghwan Kim; Soohyung Park; In Seok Seo; Mehmet Suha Yazici; et al. (Chemical Engineering Journal, 2026)

Bee pollination enhances fruit development and delays ripening by modulating the transition of ethylene biosynthesis and receptor dynamics in tomato (Solanum lycopersicum L.) - Ji Yeong Ham; Yong-Tae Kim; Jong Hwa Shin; Keono Kim; Jeehye Sung; Chuleui Jung; Hataitip Nimitkeatkai; Bongsu Choi; Byung-Chun In (Horticulture, Environment, and Biotechnology, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

Patterns of genomic variation and population structure suggest the strong influence of allopatry between peninsular and island distributions of seashore spatulate aster on the Korean east coast region - Homervergel G. Ong; Eui‑Kwon Jung; Woo-Ho Kim; Yong‑In Kim; Jung‑Hoon Lee; Bo‑Yun Kim; Young‑Dong Kim (Journal of Plant Research, 2026)

Spatial heterogeneity of food web structure driven by glacial retreat in Marian Cove, Antarctica: linking environmental DNA interconnections - Kyu-Young Shim; In-Cheol Yeo; Jun-Oh Min; Jeong-Hoon Kim; Sun-Yong Ha; Chang-Bum Jeong (Marine Life Science & Technology, 2026)

Quantifying the joint effects of soil salinity and fertility on rice growth and yield variability in coastal paddies of southwestern Korea - Seo-Woo Park; Nuri Baek; Se-In Lee; Eun-Seo Shin; Hyun-Jin Park; Han-Yong Kim; Kyo-Suk Lee; Kwang-Seung Lee; Nurgul Kitir Sen; Woo-Jung Choi (Journal of Soils and Sediments, 2026)

Ubiquilin 1 Inhibits intracellular proliferation of Salmonella enterica serovar Typhimurium through Xenophagy - In Sook Jeon; Yong-Hee Lee; Jin Tae Hong; Won Seop Kim; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2026)

Pollution characteristics of PM2.5 and PM1.0 at urban and background sites in South Korea: Focusing on health risks of PAHs and heavy metals - Sang-Jin Lee; Ho-Young Lee; In-Gyu Cho; Seong-Joon Kim; Ji Yi Lee; Hye-Jung Shin; Young Sung Ghim; Yong Pyo Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Comparison of the Growth and Internal Quality of Red Radish (Raphanus sativus L. cv. Cherry One) Cultivated Under Different Hydroponic Systems and LED Light Qualities - Ah Young Shin; Joo Hwan Lee; Yong Beom Kwon; Yu Jin Kang; In-Lee Choi; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2026)

Hydramethylnon-induced autophagy and apoptosis in human bronchial epithelial cells by homeostatic changes - Yeon-Ho Kang; Sou Hyun Kim; Hye-Jin Jeong; Ah-Yoon Song; Hye-In Park; Eun-Hye Kim; Young-Suk Jung; Yong Joo Park (Toxicology, 2026)

Biochemical composition and bioavailability of sedimentary organic matter in two contrasting intertidal flats of Korea - Mi Sun Yun; Su In Kim; Jun-Oh Min; Sun-Yong Ha; Jae Hyeok Shin; Sunghan Kim; Seung-Il Nam; Ho Kyung Ha (Marine Pollution Bulletin, 2026)

Deep Learning-Based Prediction of Ship Roll Motion with Monte Carlo Dropout - Gi-yong Kim; Chaeog Lim; Sang-jin Oh; In-hyuk Nam; Yu-mi Lee; Sung-chul Shin (Journal of Marine Science and Engineering, 2025)
Accurate prediction of ship roll motion is essential for safe and autonomous navigation. This study presents a deep learning framework that estimates both roll motion and epistemic uncertainty using Monte Carlo (MC) Dropout. Two architectures, a Long Short-Term Memory (LSTM) network and a Transformer encoder, were trained on HydroD–Wasim simulations covering various sea states, speeds, and damage conditions, and validated with real voyage data from two ferries, showing complementary performance, where LSTM achieved higher accuracy and Transformer provided more reliable confidence intervals. Model performance was evaluated by mean squared error (MSE), prediction interval coverage probability (PICP), and prediction interval normalized average width (PINAW). The LSTM achieved lower MSE, showing superior deterministic accuracy, while the Transformer produced higher PICP and wider PINAW, indicating more reliable uncertainty estimation. Results confirm that MC Dropout effectively quantifies epistemic uncertainty, improving the reliability of deep learning–based ship motion forecasting for intelligent maritime operations.

Plant-specific crop evapotranspiration estimation system for greenhouse tomatoes using convolutional neural network and rail-based monitoring device - Min-Seok Gang; Hak-Jin Kim; Sung Kwon Park; Woo-Jae Cho; Taehyeong Kim; Tae In Ahn; Joon Yong Kim; Kue-Seung Hwang (Computers and Electronics in Agriculture, 2025)

Plant hormones interact to control postharvest quality in cut Rosa hybrida L. flowers and resistance to Botrytis cinerea - Suong Tuyet Thi Ha; Ji Yeong Ham; Yong-Tae Kim; Byung-Chun In (Horticulture, Environment, and Biotechnology, 2025)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

Physical, mechanical, and microstructural characterization of NUW-LHT-5M lunar highland simulant through spark plasma sintering - In Kyu Jeon; Yong-Rak Kim; Douglas L. Rickman (Advances in Space Research, 2025)

FOXO3a upregulates DNA repair activities by transcriptional activation of target genes and provides the resistance to gamma radiation and the extension of lifespan in mouse - Gozde Inci; Madhuri Shende Warkad; Beom-Goo Kang; Sung-Ok Kim; Na-Kyung Lee; Jee-In Heo; Seong-Hoon Park; Jeong-Hyun Kim; Hong-Jun Kang; Chae-Ha Kim; Byung-Hak Kim; Sang-Jae Park; et al. (Biogerontology, 2025)

Study on modulation of inflammation expression by Brassica oleracea L. leaves extract - Jung-Wook Kang; Dan-Hee Yoo; Hyo-Min Kim; Ji-Won Hur; Kyeung-A Kwon; Kyung-Eun Lee; Min-Yeong Kim; Yong-Jun Kwon; Su-Bin Yu; Ju-Hyun Park; In-Chul Lee (Phytochemistry Letters, 2025)

Macluraparishin C Enhances Neuroprotection Against Oxidative Stress-Induced Neurodegeneration by Activating the Antioxidant/MAPK Signaling Pathway - Md Shiblee Sadik Sabuj; Md Sadikul Islam; Md Rashedunnabi Akanda; Joonseok Lee; Ryunhee Kim; Seung Hyun Lee; Ye Ji Kim; Jin Min Oh; Hyeon Gyeong Ro; In-Shik Kim; Dongchoon Ahn; Sang-Youel Park; et al. (Molecular Neurobiology, 2025)

Effects of exogenous L-glutamic acid and supplemental LED lighting on the growth and yield of Paprika - Yong Beom Kwon; Joo Hwan Lee; Min Ji Kim; Da Young Lee; In-Lee Choi; Hyuk Sung Yoon; Yongduk Kim; Jidong Kim; Ho-Min Kang (Horticulture, Environment, and Biotechnology, 2025)

Polymer semiconductor-coated 3D bilayer cellulose nanofiber/polydimethylsiloxane aerogel for enhanced solar-driven interfacial water evaporation - Keerthnasre Dhandapani; Gayoung Ham; Hossein Fattahimoghaddam; In Ho Kim; Hyojung Cha; Xiaowu Tang; Da Wan Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Molecular analysis of insecticide resistance mutation frequencies in five cockroach species from Korea - Hyun Kyu Shin; Susie Cho; Gang Chan Lee; Do Eun Lee; Heung Chul Kim; In Yong Lee; Chung Hyun Ko; Soon-il Kim; Seong Soo Kim; Ju Hyeon Kim; Si Hyeock Lee (Pesticide Biochemistry and Physiology, 2025)

Estimation of BPA, BPS, and BPF exposure levels in the general Korean population using the physiologically-based toxicokinetic model and human urinary biomonitoring for risk assessment - Min-Ju Kim; Yong-Kook Kwon; Hyung-Jun Kim; Dong-Gyun Han; In-Soo Yoon; Seungyoung Park; Gunyoung Lee; Hye Young Lee (International Journal of Hygiene and Environmental Health, 2025)

Beyond ion size: How phase transitions in NaBi batteries enable superior rate performance to LiBi counterparts - Young-Hoon Kim; Yeong-In Yoon; Xiangmei Li; Young-Kwon Kim; Haiwon Lee; Jae-Chul Lee; Yong-Seok Choi (Chemical Engineering Journal, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Evaluating the immunomodulation effects of live lactic acid bacteria from kimchi on Transwell Caco-2 monolayer permeability - Jin Yong Kang; Daun Kim; So Yeong Mun; Ji Young Jeong; Namhee Kim; In Min Hwang; Ho Myeong Kim (Food Bioscience, 2025)

Interaction between plant hormones in response to Botrytis cinerea infection in cut flowers with differential tissue sensitivity to ethylene - Suong Tuyet Thi Ha; Ji Yeong Ham; Yong-Tae Kim; Byung-Chun In (Postharvest Biology and Technology, 2025)

Multiple measures to mitigate methane emissions from organic rice fields: a review and future challenges - Nuri Baek; Se-In Lee; Husna Israt Pia; Seo-Woo Park; Eun-Seo Shin; Miwa M. Yashima; Han-Yong Kim; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2025)

Metabarcoding for the Monitoring of the Microbiome and Parasitome of Medically Important Mosquito Species in Two Urban and Semi-urban Areas of South Korea - Xavier Chavarria; Jun Ho Choi; Singeun Oh; Myungjun Kim; Dongjun Kang; In-Yong Lee; Yun Soo Jang; Myung-hee Yi; Tai-Soon Yong; Ju Yeong Kim (Current Microbiology, 2025)

Spatial variations of ascidian diets in a glacial retreated fjord of the West Antarctic Peninsula - Dong-U Kim; In-Young Ahn; Jong-Ku Gal; Sun-Yong Ha; Jong Seong Khim (Marine Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

One-pot modular nanogel platform utilizing phenolic gelatin-polyethyleneimine for small RNA delivery - Kyoungmin Park; Jie Zheng; Jeong-Eun Yoo; Jonggun Kim; In-Yong Kim; Seungkwon You (Chemical Engineering Journal, 2025)

Direct aluminate precipitation technique with a phase transformation strategy for selective lithium extraction from Uyuni brine - Hee Seo Kim; Yong Jae Suh; Dae-Woo Kim; Heeji Yoo; Hye-Jin Hong; In-Su Park (Chemical Engineering Journal, 2025)

Pre and postharvest application of nano silver improves gray mold disease resistance and longevity of cut roses - Suong Tuyet Thi Ha; Yong-Tae Kim; Byung-Chun In (Horticulture, Environment, and Biotechnology, 2025)

Population genetics analysis based on mitochondrial cytochrome c oxidase subunit I (CO1) gene sequences of Cottus koreanus in South Korea - Bong Han Yun; Yong Hwi Kim; Ho-Seop Han; In-Chul Bang (Genes & Genomics, 2025)

Nationwide analysis of greenhouse effluents reveals robustness of crops as a modulator of ambient stoichiometry - Tae In Ahn; Jung-Seok Yang; Yong-Hoon Im; Young Jik Youn; Dahae Kim; Ju Young Lee (Journal of Cleaner Production, 2024)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

Establishment of a small-cell lung cancer (SCLC) mouse model using enhanced cancer stem-cell-functioning 3D SCLC spheroids - Yong Hun Jung; In Kyoung Kim; So Young Eom; Hyunsoo Kim; Kyungwon Park; Seok Chung; Sang Haak Lee; Chang Dong Yeo; Hye Joung Kim; Hye Seon Kang (Molecular & Cellular Toxicology, 2024)

A systematic review and BMD modeling approach to develop an AOP for humidifier disinfectant-induced pulmonary fibrosis and cell death - Donghyun Kim; Yusun Shin; Jong-In Park; Donghyeon Lim; Hyunjoon Choi; Seongwon Choi; Yong-Wook Baek; Jungyun Lim; Younghee Kim; Ha Ryong Kim; Kyu Hyuck Chung; Ok-Nam Bae (Chemosphere, 2024)

Microcystis abundance is predictable through ambient bacterial communities: A data-oriented approach - Mingyeong Kang; Dong-Kyun Kim; Ve Van Le; So-Ra Ko; Jay Jung Lee; In-Chan Choi; Yuna Shin; Kyunghyun Kim; Chi-Yong Ahn (Journal of Environmental Management, 2024)

Carboxymethyl cellulose-based rotigotine nanocrystals-loaded hydrogel for increased transdermal delivery with alleviated skin irritation - Jun Soo Park; Jae Hee Seo; Min Young Jeong; In Gyu Yang; Ji Seong Kim; Jin Hwan Kim; Myoung Jin Ho; Sung Giu Jin; Min Koo Choi; Yong Seok Choi; Myung Joo Kang (Carbohydrate Polymers, 2024)

Relationship between rheological properties, sensory perception, and overall acceptability of thickened liquids for dysphagia in young and old healthy individuals - Yong Gi Chun; Yun Jeong Kim; In Young Lee; Eun Young Jeon; Bum-Keun Kim (Food Research International, 2024)

Evaluating the potential of optimized PCM-wallboards for reducing energy consumption and CO2 emission in buildings - Hussein Al Jebaei; Ashrant Aryal; In Kyu Jeon; Abdullah Azzam; Yong-Rak Kim; Juan-Carlos Baltazar (Energy and Buildings, 2024)

Ether vs. Carbonate solvents in Na–CuS Batteries: Impact on anode Morphology, SEI Formation, and desolvation dynamics - Young-Hoon Kim; Son-Jae Sim; Yeong-In Yoon; Yong-Seok Choi; Hong-Kyu Kim; Jae-Chul Lee (Chemical Engineering Journal, 2024)

Sex, age, and species differences of perfluorooctanoic acid modeled by flow- versus permeability-limited physiologically-based pharmacokinetic models - Go-Wun Choi; Dong Wook Kang; Ju Hee Kim; Seok-jin Cho; Yong-Bok Lee; In-Ho Kwon; Hea-Young Cho (Toxicology, 2024)

Decoupling stiffness and toughness of self-healing hydrogels for complex tissue regeneration via 3D bioprinting - Hyun Seung Kim; Jun Seo Kim; Jiwon Hwang; In Young Lee; Kuen Yong Lee (Chemical Engineering Journal, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Enhanced solar-driven thermoelectric power generation and water desalination via hydrothermally synthesized degenerately doped copper selenide nanocrystals composited with polydimethylsiloxane - Keerthnasre Dhandapani; Hossein Fattahimoghaddam; In Ho Kim; Tae Kyu An; Yong Jin Jeong (Desalination, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Physicochemical characterization and environmental stability of a curcumin-loaded Pickering nanoemulsion using a pea protein isolate-dextran conjugate via the Maillard reaction - Yun Jeong Kim; Hae In Yong; Yong Gi Chun; Bum-Keun Kim; Min Hyeock Lee (Food Chemistry, 2024)

Abiotic and stand age-induced changes in tree diversity and size inequality regulate aboveground biomass and soil organic carbon stock in temperate forests of South Korea - Yong-Ju Lee; Hae-In Lee; Chang-Bae Lee; Kyeong-Hak Lee; Rae-Hyun Kim; Arshad Ali (CATENA, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Application of oyster shells in the remediation of marine sediment - Maheshkumar Prakash Patil; Dae In Lee; Un-Gi Hwang; Yong Soo Joo; Kyunghoi Kim (Journal of Soils and Sediments, 2024)

TRIAD method to assess ecological risks of contaminated soils in abandoned mine sites - Dokyung Kim; Jin Il Kwak; Tae-Yang Lee; Lia Kim; Haemi Kim; Sun Hwa Nam; Wonjae Hwang; June Wee; Yong Ho Lee; Songhee Kim; Ji-In Kim; Sunhee Hong; et al. (Journal of Hazardous Materials, 2024)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Performance analysis of heat pipe-based passive in-core decay heat removal system for the small modular reactor design with MARS-KS code - Ji Yong Kim; Ye Yeong Park; In Cheol Bang (Annals of Nuclear Energy, 2023)

In situ electrolyte replenishment with atmospheric pressure-chemical/electrochemical vapour deposition for molten carbonate fuel cells - Kab In Kim; Jae Kwan Bae; Emilio Audasso; Albert Won Cho; Young Bae Jun; Hyun Seo Park; Seong-Cheol Jang; Yong Soo Cho; Han Sung Kim; Sun-Hee Choi; Sung Pil Yoon (Chemical Engineering Journal, 2023)

Mycotoxins in food and feed: toxicity, preventive challenges, and advanced detection techniques for associated diseases - Debasish Kumar Dey; Ji In Kang; Vivek K. Bajpai; Kwanwoo Kim; Hoomin Lee; Sonam Sonwal; Jesus Simal-Gandara; Jianbo Xiao; Sajad Ali; Yun Suk Huh; Yong-Kyu Han; Shruti Shukla (Critical Reviews in Food Science and Nutrition, 2023)

Microplastic contamination in groundwater of rural area, eastern part of Korea - Eunju Jeong; Young-In Kim; Jin-Yong Lee; Maimoona Raza (Science of The Total Environment, 2023)

Dual facet passivation of silver halometallate for eco-friendly silver bismuth sulfide near IR photodetector - Ashish Sharma; Hanjae Kim; Gunhee Kim; Jinhyeon Kang; Cheong Beom Lee; Sung Yong Bae; Hochan Song; Kyeounghak Kim; Jong Hyun Kim; In Hwan Jung; Dong-Won Kang; Jihoon Lee; et al. (Chemical Engineering Journal, 2023)

Safety concerns regarding impurities in L-Tryptophan associated with eosinophilia myalgia syndrome - Soo Min Ko; Ji-Eun Park; In Kyung Heo; Yong Uk Shin; Yang Hee Kim; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Disruption of type I interferon pathway and reduced production of IFN-α by parabens in virus-infected dendritic cells - In-Gu Lee; Yong-Hyun Joo; Hoyeon Jeon; Jung-Woong Kim; Young-Jin Seo; So-Hee Hong (Genes & Genomics, 2023)

Evaluation of fermented soybean meal and edible insect hydrolysates as potential serum replacement in pig muscle stem cell culture - Cho Hyun Kim; Hyun Jung Lee; Doo Yeon Jung; Minsu Kim; Hyun Young Jung; Heesang Hong; Yun-Sang Choi; Hae In Yong; Cheorun Jo (Food Bioscience, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Microplastic contamination in groundwater on a volcanic Jeju Island of Korea - Young-In Kim; Eunju Jeong; Jin-Yong Lee; Rogers Wainkwa Chia; Maimoona Raza (Environmental Research, 2023)

Electronic structure reconfiguration of nickel–cobalt layered double hydroxide nanoflakes via engineered heteroatom and oxygen-vacancies defect for efficient electrochemical water splitting - Kai Chen; Yong-Hua Cao; Sunny Yadav; Gyu-Cheol Kim; Zheng Han; Wenmeng Wang; Wei-Jin Zhang; Vandung Dao; In-Hwan Lee (Chemical Engineering Journal, 2023)

Effects of edible insect extracts on the antioxidant, physiochemical, and microbial properties of Tteokgalbi during refrigerated storage - Hae In Yong; Tae-Kyung Kim; Ji Yoon Cha; Jae Hoon Lee; Min-Cheol Kang; Samooel Jung; Yun-Sang Choi (Food Bioscience, 2023)

A rice seed-specific glycine-rich protein OsDOR1 interacts with GID1 to repress GA signaling and regulates seed dormancy - Sooyeon Kim; Sun Mi Huh; Hay Ju Han; Gang Seob Lee; Yong-Sic Hwang; Mi Hyun Cho; Beom-Gi Kim; Ji Sun Song; Joo Hee Chung; Myung Hee Nam; Hyeonso Ji; Kyung-Hwan Kim; et al. (Plant Molecular Biology, 2023)

High-pressure induced structural modification of porcine myofibrillar protein and its relation to rheological and emulsifying properties - Min Hyeock Lee; Hae In Yong; Yun Jeong Kim; Yun-Sang Choi (Meat Science, 2023)

Assessment of sulfidated nanoscale zerovalent iron for in-situ remediation of cadmium-contaminated acidic groundwater at a zinc smelter - In-Gyu Song; Yu-Gyeong Kang; Jae-Hwan Kim; Hakwon Yoon; Woo Yong Um; Yoon-Seok Chang (Journal of Hazardous Materials, 2023)

Peptides inhibiting angiotensin-I-converting enzyme: Isolation from flavourzyme hydrolysate of Protaetia brevitarsis larva protein and identification - Jae Hoon Lee; Tae-Kyung Kim; Hae In Yong; Ji Yoon Cha; Kyung-Mo Song; Hyo Geun Lee; Jun-Geon Je; Min-Cheol Kang; Yun-Sang Choi (Food Chemistry, 2023)

3-Hydroxymorphinan protects against hypoxia-induced cell death in primary astrocyte by regulating Ca2+ influx and the glutamate homeostasis - Ok-Hyeon Kim; Gyeong Yun Lee; Kyung Yong Kim; Jong In Son; Tae Woo Jung; Ji Hoon Jeong; Joon Seok Bang; Hyoung-Chun Kim; Yoon Hee Chung; Hyun Jung Lee (Molecular & Cellular Toxicology, 2023)

Description of Microbacterium neungamense sp. nov. isolated from a hot spring - Dariimaa Ganbat; Ga Eul Jeong; DoKyung Oh; Dong-Woo Lee; Yong-Jik Lee; Seong-Bo Kim; In-Tae Cha; Won-Jae Chi; Seul-Ki Park; Jung-Sook Lee; Sang-Jae Lee (Archives of Microbiology, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Worldwide patent trend analysis of herbicide-resistant genes - Beom Yong Kim; In-Jung Kim (Plant Biotechnology Reports, 2022)

Population genomics study for the conservation management of the endangered shrub Abeliophyllum distichum - Jung-Hoon Lee; Homervergel G. Ong; Bo-Yun Kim; Yong-In Kim; Eui-Kwon Jung; Myong Gi Chung; Young-Dong Kim (Conservation Genetics, 2022)
Natural monuments are IUCN Category III protected areas that play an important role in biodiversity conservation as they provide species refuge and allow species migration. Despite their status, natural monuments are often confined to cultural and fragmented landscapes due to anthropogenic land-use demands. In this population genomic study, we surveyed 11 populations of the endemic shrub Abeliophyllum distichum Nakai (Oleaceae), including five natural monument habitats, covering its range-wide distribution in South Korea. Using 2,254 SNPs as markers, our results showed a mean expected heterozygosity ( He ) of 0.319, with populations in the central distribution showing significantly higher He than those at the periphery. There was no significant heterozygote deficiency and inbreeding among studied populations overall ( F IS = −0.098), except for a single natural monument population (GS-NM147). Population structure and differentiation was moderate to high ( F ST = 0.196), while recent gene flow between populations appeared weak, which can be attributed to the fragmented distribution and the outcrossing mating system of the heterostylous plant. Based on these findings, we provide suggestions for the population conservation and management of this endangered species.

Biocontrol of fire blight via microcapsule-mediated delivery of the bacterial antagonist Pantoea agglomerans E325 to apple blossoms - In-Yong Kim; Benjamin Lew; Youfu Zhao; Schuyler S. Korban; Hyungsoo Choi; Kyekyoon Kim (BioControl, 2022)

Persistent Continental Shelf Carbon Sink at the Ieodo Ocean Research Station in the Northern East China Sea - Kitack Lee; Ja-Myung Kim; Gyeong-Seok Lee; Eunil Lee; Jin-Yong Jeong; Jaeik Lee; In-Seong Han (Frontiers in Marine Science, 2022)
Hourly (2017–2021) to seasonal (2015–2021) inorganic C data were collected at the Ieodo Ocean Research Station (32.07°N and 125.10°E) in the northern East China Sea (ECS), located under the influence of the nutrient-rich Changjiang Diluted Water (CDW). An increase in phytoplankton biomass from April to mid-August (the warming period) equalized much of the temperature-driven increase in the surface pCO 2 and thus, made the northern ECS a moderate sink of atmospheric CO 2 . From November to March (the cooling period), a large pCO 2 reduction, driven by a temperature reduction, and a high air–sea CO 2 exchange rate, because of high windspeeds, transformed the basin into a substantial CO 2 sink, yielding an annual net C uptake of 61.7 g C m –2 yr –1 . The effects of biological production and temperature change on seawater pCO 2 (and thus, the net air–sea CO 2 flux) were decoupled each season and acted in concert to increase the net annual CO 2 sink by the region. The present study provided the observational and mechanistic lines of evidence for confirming “continental shelf C pump”—a mechanism in the shallow waters of the continental shelves that accumulate a significant amount of C ( via reinforced cooling and promoted biological C uptake) that is transported from the basin surface waters to the interior of the adjacent deep ocean. In the future, an increasing input of anthropogenic nutrients into the northern ECS is likely to make the region a stronger CO 2 sink.

Improvement of IgA Nephropathy and Kidney Regeneration by Functionalized Hyaluronic Acid and Gelatin Hydrogel - Sureerat Khunmanee; So Young Chun; Yun-Sok Ha; Jun Nyung Lee; Bum Soo Kim; Wei-Wei Gao; In Yong Kim; Dong Keun Han; Seungkwon You; Tae Gyun Kwon; Hansoo Park (Tissue Engineering and Regenerative Medicine, 2022)

Immobilization of Laccase Through Inorganic-Protein Hybrids Using Various Metal Ions - Sanjay K. S. Patel; Vipin C. Kalia; Sang-Yong Kim; Jung-Kul Lee; In-Won Kim (Indian Journal of Microbiology, 2022)

Double-blind randomized placebo-controlled study of the efficacy and safety of hair loss prevention shampoo containing salicylic acid, panthenol, and niacinamide in alopecia patients - Hee-Taek Kim; Hye-Su Park; Yong-Min Kim; In-Chul Lee; Sang-Jun Lee; Jae-Suk Choi (Toxicology and Environmental Health Sciences, 2022)

The effect of gamma-irradiation on the changes of photosynthetic efficiency in Kanpei (Citrus unshiu × C. sinensis) - Seong Heo; Jung Min Choi; Anh Tuan Le; Chang-Ho Eun; In-Jung Kim; Yong Suk Chung (Plant Biotechnology Reports, 2022)

Circulating microRNA miR-137 as a stable biomarker for methamphetamine abstinence - Baeksun Kim; Sung Hyun Tag; Yong Sik Kim; Sung Nam Cho; Heh-In Im (Psychopharmacology, 2022)
Objective Stimulant use instigates abstinence syndrome in humans. miRNAs are a critical component for the pathophysiology of stimulant abstinence. Here we sought to identify a miRNA marker of methamphetamine abstinence in the circulating extracellular vesicles (cEVs). Methods miR-137 in the cEVs was quantified by qPCR in thirty-seven patients under methamphetamine abstinence and thirty-five age-matched healthy controls recruited from 2014 to 2016 from the general adult population in a hospital setting, Seoul, South Korea. Diagnostic power was evaluated by area under curve in the receiver-operating characteristics curve and other multiple statistical parameters. Results Patients under methamphetamine abstinence exhibited a significant reduction in cEV miR-137. Overall, cEV miR-137 had high potential as a blood-based marker of methamphetamine abstinence. cEV miR-137 retained the diagnostic power irrespective of the duration of methamphetamine abstinence or methamphetamine use. Interestingly, cEV miR-137 interacted with age: Control participants displayed an aging-dependent reduction of cEV miR-137, while methamphetamine-abstinent patients showed an aging-dependent increase in cEV miR-137. Accordingly, cEV miR-137 had variable diagnostic power depending on age, in which cEV miR-137 more effectively discriminated methamphetamine abstinence in the younger population. Duration of methamphetamine use or abstinence, cigarette smoking status, depressive disorder, or antidepressant treatment did not interact with the methamphetamine abstinence-induced reduction of cEV miR-137. Conclusion Our data collectively demonstrated that miR-137 in the circulating extracellular vesicles held high potential as a stable and accurate diagnostic marker of methamphetamine abstinence syndrome.

Neferine increases sensitivities to multiple anticancer drugs via downregulation of Bcl-2 expression in renal cancer cells - Eun-Ae Kim; Ji Hoon Jang; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2022)

Seasonal Dietary Shifts of the Gammarid Amphipod Gondogeneia antarctica in a Rapidly Warming Fjord of the West Antarctic Peninsula - In-Young Ahn; Francyne Elias-Piera; Sun-Yong Ha; Sergio Rossi; Dong-U Kim (Journal of Marine Science and Engineering, 2021)
The amphipod Gondogeneia antarctica is among the most abundant benthic organisms, and a key food web species along the rapidly warming West Antarctic Peninsula (WAP). However, little is known about its trophic strategy for dealing with the extreme seasonality of Antarctic marine primary production. This study, using trophic markers, for the first time investigated seasonal dietary shifts of G. antarctica in a WAP fjord. We analyzed δ13C and δ15N in G. antarctica and its potential food sources. The isotopic signatures revealed a substantial contribution of red algae to the amphipod diet and also indicated a significant contribution of benthic diatoms. The isotope results were further supported by fatty acid (FA) analysis, which showed high similarities in FA composition (64% spring–summer, 58% fall–winter) between G. antarctica and the red algal species. G. antarctica δ13C showed a small shift seasonally (−18.9 to −21.4‰), suggesting that the main diets do not change much year-round. However, the relatively high δ15N values as for primary consumers indicated additional dietary sources such as animal parts. Interestingly, G. antarctica and its potential food sources were significantly enriched with δ15N during the fall–winter season, presumably through a degradation process, suggesting that G. antarctica consumes a substantial portion of its diets in the form of detritus. Overall, the results revealed that G. antarctica relies primarily on food sources derived from benthic primary producers throughout much of the year. Thus, G. antarctica is unlikely very affected by seasonal Antarctic primary production, and this strategy seems to have allowed them to adapt to shallow Antarctic nearshore waters.

Relationship among floral scent intensity, ethylene sensitivity, and longevity of carnation flowers - Byung-Chun In; Suong Tuyet Thi Ha; Yong-Tae Kim; Jin Hee Lim (Horticulture, Environment, and Biotechnology, 2021)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Camellia japonica diminishes acetaminophen-induced acute liver failure by attenuating oxidative stress in mice - Weishun Tian; Jing Zhao; Byung-Kil Choo; In-Shik Kim; Dongchoon Ahn; Hyun-Jin Tae; Md Sadikul Islam; Byung-Yong Park (Environmental Science and Pollution Research, 2021)

Lactucin induces apoptosis through reactive oxygen species-mediated BCL-2 and CFLARL downregulation in Caki-1 cells - Ji Hoon Jang; Cho-Young Park; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Chuleui Jung; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2021)

Biotin and Zn2+ Increase Xylitol Production by Candida tropicalis - Gurusamy Muneeswaran; Sanjay K. S. Patel; Sanath Kondaveeti; Ramasamy Shanmugam; Krishnasamy Gopinath; Virendra Kumar; Sang-Yong Kim; Jung-Kul Lee; Vipin Chandra Kalia; In-Won Kim (Indian Journal of Microbiology, 2021)

Orphan nuclear receptor ERRγ regulates hepatic TGF-β2 expression and fibrogenic response in CCl4-induced acute liver injury - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina Kim; In-Kyu Lee; Sung Jin Cho; Don-Kyu Kim; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2021)

Functional dissection of the phosphotransferase system provides insight into the prevalence of Faecalibacterium prausnitzii in the host intestinal environment - Deborah Kang; Hyeong‐In Ham; Seung‐Hwan Lee; Yong‐Joon Cho; Yeon‐Ran Kim; Chang‐Kyu Yoon; Yeong‐Jae Seok (Environmental Microbiology, 2021)
Summary Faecalibacterium prausnitzii is a dominant member of healthy human colon microbiota, regarded as a beneficial gut bacterium due to its ability to produce anti‐inflammatory substances. However, little is known about how F. prausnitzii utilizes the nutrients present in the human gut, influencing its prevalence in the host intestinal environment. The phosphoenolpyruvate (PEP):carbohydrate phosphotransferase system (PTS) is a widely distributed and highly efficient carbohydrate transport system found in most bacterial species that catalyses the simultaneous phosphorylation and import of cognate carbohydrates; its components play physiological roles through interaction with other regulatory proteins. Here, we performed a systematic analysis of the 16 genes encoding putative PTS components (2 enzyme I, 2 HPr, and 12 enzyme II components) in F. prausnitzii A2‐165. We identified the general PTS components responsible for the PEP‐dependent phosphotransfer reaction and the sugar‐specific PTS components involved in the transport of two carbohydrates, N ‐acetylglucosamine and fructose, among five enzyme II complexes. We suggest that the dissection of the functional PTS in F. prausnitzii may help to understand how this species outcompetes other bacterial species in the human intestine.

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

Rhus vernicifera Laccase Immobilization on Magnetic Nanoparticles to Improve Stability and Its Potential Application in Bisphenol A Degradation - Sanjay K. S. Patel; Rahul K. Gupta; Sang-Yong Kim; In-Won Kim; Vipin C. Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Treatment with silicon fertilizer induces changes in root morphological traits in soybean (Glycine max L.) during early growth - Yong Suk Chung; Se-Hun Kim; Chang- Wook Park; Chae -In Na; Yoonha Kim (Journal of Crop Science and Biotechnology, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

Breakthroughs in the fabrication of electrospun-nanofiber-supported thin film composite/nanocomposite membranes for the forward osmosis process: A review - M. Obaid; Mohammad Ali Abdelkareem; Seungho Kook; Hak-Yong Kim; Nidal Hilal; Noreddine Ghaffour; In S. Kim (Critical Reviews in Environmental Science and Technology, 2020)

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Identification of the prion-related protein gene (PRNT) sequences in various species of the Cervidae family - In-Soon Roh; Yong-Chan Kim; Hyo-Jin Kim; Sae-Young Won; Min-Ju Jeong; Hae-Eun Kang; Hyun-Joo Sohn; Byung-Hoon Jeong (Molecular Biology Reports, 2020)

CORM-2-Solid Lipid Nanoparticles Maintain Integrity of Blood-Spinal Cord Barrier After Spinal Cord Injury in Rats - Hari Prasad Joshi; Hemant Kumar; Un Yong Choi; Yong Cheol Lim; Hyemin Choi; Juri Kim; Jae Won Kyung; Seil Sohn; Kyoung-Tae Kim; Jin-Ki Kim; In-Bo Han (Molecular Neurobiology, 2020)

Characterization of Cellobiohydrolases from Schizophyllum commune KMJ820 - Sanath Kondaveeti; Sanjay K. S. Patel; Janghun Woo; Ji Hyang Wee; Sang-Yong Kim; Riyadh I. Al-Raoush; In-Won Kim; Vipin Chandra Kalia; Jung-Kul Lee (Indian Journal of Microbiology, 2020)

Attenuation of Tumor Necrosis Factor-α Induced Inflammation by Umbilical Cord-Mesenchymal Stem Cell Derived Exosome-Mimetic Nanovesicles in Endothelial Cells - Kyoung-Won Ko; Yong-In Yoo; Jun Yong Kim; Bogyu Choi; Sung-Bin Park; Wooram Park; Won-Kyu Rhim; Dong Keun Han (Tissue Engineering and Regenerative Medicine, 2020)

4-MeO-PCP and 3-MeO-PCMo, new dissociative drugs, produce rewarding and reinforcing effects through activation of mesolimbic dopamine pathway and alteration of accumbal CREB, deltaFosB, and BDNF levels - Arvie Abiero; Chrislean Jun Botanas; Raly James Custodio; Leandro Val Sayson; Mikyung Kim; Hyun Jun Lee; Hee Jin Kim; Kun Won Lee; Youngdo Jeong; Joung-Wook Seo; In Soo Ryu; Yong Sup Lee; et al. (Psychopharmacology, 2020)

An inverse agonist of estrogen-related receptor γ regulates 2-arachidonoylglycerol synthesis by modulating diacylglycerol lipase expression in alcohol-intoxicated mice - Yoon Seok Jung; Yong-Hoon Kim; Kamalakannan Radhakrishnan; Jina kim; Don-Kyu Kim; Ji-Hyeok Lee; Hyunhee Oh; In-Kyu Lee; Wook Kim; Sung Jin Cho; Cheol Soo Choi; Steven Dooley; et al. (Archives of Toxicology, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

A Yellow Sea Monitoring Platform and Its Scientific Applications - Yong Sun Kim; Chan Joo Jang; Jae Hoon Noh; Kyung-Tae Kim; Jae-Il Kwon; Yongchim Min; Jongmin Jeong; Jaeik Lee; In-Ki Min; Jae-Seol Shim; Do-Seong Byun; Jinkwon Kim; et al. (Frontiers in Marine Science, 2019)

Multidrug-resistant Acinetobacter baumannii infection in lung transplant recipients: risk factors and prognosis - Dong Hyun Oh; Yong Chan Kim; Eun Jin Kim; In Young Jung; Su Jin Jeong; Song Yee Kim; Moo Suk Park; Anes Kim; Jin Gu Lee; Hyo Chae Paik (Infectious Diseases, 2019)

Image Analysis for Measuring Disease Symptom to Bacterial Soft Rot in Potato - Unseok Lee; Renato Rodrigues Silva; Changsoo Kim; Hyoungseok Kim; Seong Heo; In Sung Park; Wook Kim; Shelley Jansky; Yong Suk Chung (American Journal of Potato Research, 2019)

Stem Cells Seeded on Multilayered Scaffolds Implanted into an Injured Bladder Rat Model Improves Bladder Function - Kshitiz Raj Shrestha; Seung Hwan Jeon; Ae Ryang Jung; In Gul Kim; Ga Eun Kim; Yong Hyun Park; Soo Hyun Kim; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Copper Ferrite Magnetic Nanoparticles for the Immobilization of Enzyme - Sachin V. Otari; Sanjay K. S. Patel; Sang-Yong Kim; Jung Rim Haw; Vipin C. Kalia; In-Won Kim; Jung-Kul Lee (Indian Journal of Microbiology, 2019)

Improvement of blood culture contamination rate, blood volume, and true positive rate after introducing a dedicated phlebotomy team - Moonsuk Bae; Hae In Kim; Joung Ha Park; Byung-Han Ryu; Jeonghyun Chang; Heungsup Sung; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Regulatory role of Wdr24 in autophagy activity during zebrafish embryogenesis - Yong-Il Kim; In-Koo Nam; Jae-Young Um; Seong-Kyu Choe (Molecular & Cellular Toxicology, 2019)

Combined Treatment with Low-Level Laser and rhBMP-2 Promotes Differentiation and Mineralization of Osteoblastic Cells under Hypoxic Stress - Jin-Ho Heo; Jeong-Hun Choi; In-Ryoung Kim; Bong-Soo Park; Yong-Deok Kim (Tissue Engineering and Regenerative Medicine, 2018)

Physiological Characteristics and Related Biochemical Parameters of Snow Algae from King George Island, Antarctica - Bo Kyung Kim; HyoungMin Joo; Boyeon Lee; Dong-Hun Lee; In-Young Ahn; Sun-Yong Ha (Ocean Science Journal, 2018)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Recent Primary Production and Small Phytoplankton Contribution in the Yellow Sea during the Summer in 2016 - Hyo Keun Jang; Jae Jung Kang; Jae Hyung Lee; Myungjoon Kim; So Hyun Ahn; Jin-Yong Jeong; Mi Sun Yun; In-Seong Han; Sang Heon Lee (Ocean Science Journal, 2018)

Inverse agonist of ERRγ reduces cannabinoid receptor type 1-mediated induction of fibrinogen synthesis in mice with a high-fat diet-intoxicated liver - Yaochen Zhang; Don-Kyu Kim; Yoon Seok Jung; Yong-Hoon Kim; Yong Soo Lee; Jina Kim; Won-IL Jeong; In-Kyu Lee; Sung Jin Cho; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Elevated CO2 concentration affected pine and oak litter chemistry and the respiration and microbial biomass of soils amended with these litters - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Hye-In Yang; Kwang-Seung Lee; Young-Han Lee; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Optimization of TILLING system based on capillary electrophoresis for targeted selection of pepper gene mutants - Han Sol Kang; Sang Hoon Kim; Sang Woo Lee; Se Won Kim; Jaihyunk Ryu; Jin-Baek Kim; Seon-In Yeom; Si-Yong Kang; Yeong Deuk Jo (Horticulture, Environment, and Biotechnology, 2018)

Sustained exenatide delivery via intracapsular microspheres for improved survival and function of microencapsulated porcine islets - Benjamin Lew; In-Yong Kim; Hyungsoo Choi; Kyekyoon Kim (Drug Delivery and Translational Research, 2018)

Dendropanax morbifera Léveille extract ameliorates cesium-induced inflammation in the kidney and decreases antioxidant enzyme levels in the hippocampus - Hyo Young Jung; Hyun Jung Kwon; Kyu Ri Hahn; Dae Young Yoo; Woosuk Kim; Jong Whi Kim; Yong Jae Kim; Yeo Sung Yoon; Dae Won Kim; In Koo Hwang (Molecular & Cellular Toxicology, 2018)

Practice Patterns in Distinguishing Between Background Pain and Breakthrough Pain During Patient Education: a Korean Physician Survey - Jinyoung Shin; Do Yeun Kim; Juneyoung Lee; Youn Seon Choi; In Gyu Hwang; Sun Kyung Baek; Min Seok Seo; Jae Yong Shim (Journal of Cancer Education, 2018)

Effects of 1-methylcyclopropene (1-MCP) and polyethylene (PE) film liner treatments on the fruit quality of cold-stored ‘Gamhong’ apples - Kyoung-ook Kim; Jingi Yoo; Jinwook Lee; Nay Myo Win; Seulgi Ryu; Jeung-Sul Han; Hee-Young Jung; Myoung-Gun Choung; Yong-Deuk Kwon; Dong Hoon Lee; In-Kyu Kang (Horticulture, Environment, and Biotechnology, 2018)

An efficient and tunable parameter to improve variant calling for whole genome and exome sequencing data - Yong Ju Ahn; Kesavan Markkandan; In-Pyo Baek; Seyoung Mun; Wooseok Lee; Heui-Soo Kim; Kyudong Han (Genes & Genomics, 2018)

Erratum to: Growth and nutrient composition of platycodon grown in media amended with pellets processed with poultry feathers - In Kyung Kim; Mark S. Roh; Yong Seung Roh; Yong Kwon Yoo (Horticulture, Environment, and Biotechnology, 2017)

Growth and nutrient composition of platycodon grown in media amended with pellets processed with poultry feathers - In Kyung Kim; Mark S. Roh; Yong Seung Roh; Yong Kwon Yoo (Horticulture, Environment, and Biotechnology, 2017)

The influence of tectonic subsidence on volcaniclastic sedimentation: The Cretaceous upper Daeri Member, Wido Island, Korea - Yong Sik Gihm; Min‐Cheol Kim; Moon Son; In Gul Hwang (Island Arc, 2017)
The Daeri Member, a Cretaceous volcanic–sedimentary succession, can be divided into lower, middle, and upper parts based on vertical changes in its lithologic characters. The lower Daeri Member is composed of siliciclastic deposits formed in a semi‐arid floodplain environment, which is overlain by the middle Daeri Member consisting mainly of andesite lava flow. After the emplacement of the andesite, activities of intrabasinal normal faults created accommodation on hanging wall blocks together with the development of intrabasinal topographic relief. The upper Daeri Member occurs only in hanging wall blocks and is composed of rhyolitic volcaniclastic sediments formed during an explosive volcanic eruption. Following the eruption, owing to semi‐arid climatic conditions and the destruction of vegetation, the eruptive materials were easily remobilized and deposited by episodic sediment gravity flows, resulting in deposition of the resedimented volcaniclastic deposits with sheet‐like geometry. Away from the intrabasinal normal faults, the resedimented volcaniclastic deposits show a decrease in grain size together with changes in inferred depositional processes from debris flows to hyperconcentrated flows and supercritical sheetfloods. This suggests that the resedimented volcaniclastic deposits were stacked on alluvial fan environments induced by intrabasinal topographic relief associated with normal fault activities. In addition, episodic movement of the faults gave rise to periodic fluctuation of the accommodation and an increase in gradient of the alluvial fan surface, resulting in the development of coarsening‐upward trends in the resedimented volcaniclastic deposits. The development of the alluvial fan and the coarsening‐upward trends indicate that dynamic tectonic subsidence and concomitant changes in the intrabasinal physiographic relief influenced the depositional processes and sizes of the transported volcaniclastic sediments of the upper Daeri Member. Thus, it is necessary to carefully observe tectonic signatures in volcaniclastic successions, particularly the syneruptive lithofacies, in order to reconstruct the tectonic and volcanic histories of receiving basins.

Alternative new mesenchymal stem cell source exerts tumor tropism through ALCAM and N-cadherin via regulation of microRNA-192 and -218 - Ran Kim; Sang In Park; Chang Youn Lee; Jihyun Lee; Pilseog Kim; Sekyung Oh; Hojin Lee; Min Young Lee; Jongmin Kim; Yong-An Chung; Ki-Chul Hwang; Lee-So Maeng; et al. (Molecular and Cellular Biochemistry, 2017)

Clozapine Improves Memory Impairment and Reduces Aβ Level in the Tg-APPswe/PS1dE9 Mouse Model of Alzheimer’s Disease - Yura Choi; Ha Jin Jeong; Quan Feng Liu; Seung Tack Oh; Byung-Soo Koo; Yeni Kim; In-Won Chung; Yong Sik Kim; Songhee Jeon (Molecular Neurobiology, 2017)

Development and application of three-dimensional potential source contribution function (3D-PSCF) - In Sun Kim; Daehyun Wee; Yong Pyo Kim; Ji Yi Lee (Environmental Science and Pollution Research, 2016)

Molecular characterization of the spike and ORF3 genes of porcine epidemic diarrhea virus in the Philippines - Yong Kwan Kim; Yoon-Young Cho; Byung-Hyun An; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Van Phan Le; Dong-Jun An (Archives of Virology, 2016)

No association of CLOCK 3111T/C polymorphism with diurnal preference and sleep quality in Korean adults - Seong Jae Kim; Jung Hie Lee; Se Yong Lee; Jun-Won Hwang; In Bum Suh (Sleep and Biological Rhythms, 2016)

Phentermine induces conditioned rewarding effects via activation of the PI3K/Akt signaling pathway in the nucleus accumbens - Sa-Ik Hong; Min-Jung Kim; In-Jee You; Seung-Hwan Kwon; Shi-Xun Ma; Ji-Young Hwang; Jee-Yeon Seo; Yong-Hyun Ko; Bo Ram Lee; Seok-Yong Lee; Choon-Gon Jang (Psychopharmacology, 2016)

Mycobacterium avium MAV2052 protein induces apoptosis in murine macrophage cells through Toll-like receptor 4 - Kang-In Lee; Han-Gyu Choi; Yeo-Jin Son; Jake Whang; Kwangwook Kim; Heat Sal Jeon; Hye-Soo Park; Yong Woo Back; Seunga Choi; Seong-Woo Kim; Chul Hee Choi; Hwa-Jung Kim (Apoptosis, 2016)

Extracellular calcium-binding peptide-modified ceramics stimulate regeneration of calvarial bone defects - Ju Ang Kim; Young-Ae Choi; Hui-Suk Yun; Yong Chul Bae; Hong-In Shin; Eui Kyun Park (Tissue Engineering and Regenerative Medicine, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Effective selection of soybean cultivars to wildfire disease pathogen Pseudomonas amygdali pv. tabaci - In Jeong Kang; Seung-Han Kim; Yong Weon Seo; Min Jeong Seo; Hyeong Kwon Shim; Dong Bum Shin; Sunggi Heu (Journal of Crop Science and Biotechnology, 2015)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Monthly metabolic changes and PLS prediction of carotenoid content of citrus fruit by combined Fourier transform infrared spectroscopy and quantitative HPLC analysis - Suk Weon Kim; Myung Suk Ahn; Yong Kook Kwon; Seung Yeob Song; Jae Kwang Kim; Sun-Hwa Ha; In-Jung Kim; Jang R. Liu (Plant Biotechnology Reports, 2015)

Erratum to: Fluorescent Dye Labeled Iron Oxide/Silica Core/Shell Nanoparticle as a Multimodal Imaging Probe - Eue Soon Jang; Seung Yong Lee; Eui-Joon Cha; In-Cheol Sun; Ick Chan Kwon; Dukjoon Kim; Young Il Kim; Kwangmeyung Kim; Cheol-Hee Ahn (Pharmaceutical Research, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

A novel strain of porcine epidemic diarrhea virus in Vietnamese pigs - Yong Kwan Kim; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Eun-Hye Park; Van Phan Le; Nguyen Ba Hien; Pham Ngoc Thach; Do Hai Quynh; Tran Quang Vui; Nguyen Trung Tien; Dong-Jun An (Archives of Virology, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Molecular evolution of kobuviruses in cats - Yoon-Young Cho; Seong-In Lim; Yong Kwan Kim; Jae-Young Song; Joong-Bok Lee; Dong-Jun An (Archives of Virology, 2015)

Production of transgenic spermatozoa by lentiviral transduction and transplantation of porcine spermatogonial stem cells - Byung-Gak Kim; Yong-Hee Kim; Yong-An Lee; Bang-Jin Kim; Ki-Jung Kim; Sang-Eun Jung; Hak-Jae Chung; Seongsoo Hwang; Sun-Ho Choi; Myung Jick Kim; Dong-Hoon Kim; In Cheul Kim; et al. (Tissue Engineering and Regenerative Medicine, 2014)

Fluorescent Dye Labeled Iron Oxide/Silica Core/Shell Nanoparticle as a Multimodal Imaging Probe - Eue Soon Jang; Seung Yong Lee; Eui-Joon Cha; In-Cheol Sun; Ick Chan Kwon; Dukjoon Kim; Young Il Kim; Kwangmeyung Kim; Cheol-Hee Ahn (Pharmaceutical Research, 2014)

Nitric oxide production and scavenging in waterlogged roots of rape seedlings - Yong-Hwa Lee; Kwang-Soo Kim; Young-Seok Jang; In-Hu Choi (Genes & Genomics, 2014)

Analysis of S-locus and expression of S-alleles of self-compatible rapid-cycling Brassica oleracea ‘TO1000DH3’ - Jung Hee-Jeong; Ahmed Nasar Uddin; Park Jong-In; Thamilarasan Senthil Kumar; Kim Hye-Ran; Cho Yong-Gu; Nou Ill-Sup (Molecular Biology Reports, 2014)

Erratum to: Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Transcriptome analysis of mistletoe (Viscum album) haustorium development - Suk Min Ko; Yong Kook Kwon; Jong Hyun Kim; In-Ja Song; Hyo-Yeon Lee; Dong-Woog Choi; Jang R. Liu; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2014)

Effects of different selenium levels on growth and regulation of laccase and versatile peroxidase in white-rot fungus, Pleurotus eryngii - Yong Hyun Kim; Hyoun-Su Lee; Hyun-Jung Kwon; Bharat Bhusan Patnaik; Kung-Woo Nam; Yeon Soo Han; In-Seok Bang; Man-Deuk Han (World Journal of Microbiology and Biotechnology, 2014)

Dioscin induces caspase-independent apoptosis through activation of apoptosis-inducing factor in breast cancer cells - Eun-Ae Kim; Ji-Hoon Jang; Yun-Han Lee; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Suji Kim; Ho-Yong Sohn; Tae-Jin Lee (Apoptosis, 2014)

Molecular evidence for hybrid origin of Aster chusanensis, an endemic species of Ulleungdo, Korea - Hyunchur Shin; Sang-Hun Oh; Yongseok Lim; Chang-Woo Hyun; Seong-Hyun Cho; Yong-In Kim; Young-Dong Kim (Journal of Plant Biology, 2014)

3,4,5-Trihydroxycinnamic acid inhibits lipopolysaccharide (LPS)-induced inflammation by Nrf2 activation in vitro and improves survival of mice in LPS-induced endotoxemia model in vivo - Jae-Won Lee; Chang Jun Bae; Yong-Jun Choi; Song-In Kim; Yong-Soo Kwon; Hee Jae Lee; Sung-Soo Kim; Wanjoo Chun (Molecular and Cellular Biochemistry, 2014)

Expression of a functional recombinant chimeric protein of human hepatitis A virus VP1 and an Fc antibody fragment in transgenic tomato plants - Ho Yong Chung; Jong-Hwa Park; Hyun Ho Lee; Kyung Il Kim; Ha Young Chung; Garry Sunter; Jong Bum Kim; Wonyong Kim; In Sik Chung (Plant Biotechnology Reports, 2014)

The effect of platelet rich plasma combined with microfracture for the treatment of chondral defect in a rabbit knee - Sung Woo Huh; Asode Ananthram Shetty; Seok Jung Kim; Young Ju Kim; Nam Yong Choi; Young Joon Jun; In Joo Park (Tissue Engineering and Regenerative Medicine, 2014)

Transcriptional activation of p21WAF1/CIP1 is mediated by increased DNA binding activity and increased interaction between p53 and Sp1 via phosphorylation during replicative senescence of human embryonic fibroblasts - Hyun-Seok Kim; Jee-In Heo; Seong-Hoon Park; Jong-Yeon Shin; Hong-Jun Kang; Min-Ju Kim; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Molecular Biology Reports, 2014)

Population genetic structure of the sea bass (Lateolabrax japonicus) in Korea based on multiplex PCR assays with 12 polymorphic microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2014)

The effect of platelet rich plasma combined with microfracture for the treatment of chondral defect in a rabbit knee - Sung Woo Huh; Asode Ananthram Shetty; Seok Jung Kim; Young Ju Kim; Nam Yong Choi; Young Joon Jun; In Joo Park (Tissue Engineering and Regenerative Medicine, 2014)

Development and characterization of polymorphic microsatellite marker for an endangered freshwater fish in Korea, Gobiobotia brevibarba - Keun-Sik Kim; Hyo-Ryeon Lee; Sang-Yong Park; Myeong Hun Ko; In-Chul Bang (Conservation Genetics Resources, 2014)

Global gene expression responses to waterlogging in leaves of rape seedlings - Yong-Hwa Lee; Kwang-Soo Kim; Young-Seok Jang; Ji-Hye Hwang; Dong-Hee Lee; In-Hu Choi (Plant Cell Reports, 2014)

Development of freshwater sediment management standards for organic matters, nutrients, and metals in Korea - In Ae Huh; Yong Seok Kim; Soon Ju Yu; Stella Wong; Won Sik Shin; Hye Ok Park; Ho Jeong Kim; Hyun Woo Kim (Environmental Science and Pollution Research, 2014)

Enhanced regeneration of rabbit mandibular defects through a combined treatment of electrical stimulation and rhBMP-2 application - Junghoon Kim; Hoon Joo Yang; Tae Hyung Cho; Sung Eun Lee; Yong Doo Park; Hyun Man Kim; In Sook Kim; Young-kwon Seo; Soon Jung Hwang; Sung June Kim (Medical & Biological Engineering & Computing, 2013)

Combined effects of an antioxidant and caspase inhibitor on the reversal of hepatic fibrosis in rats - Do Young Kim; Sook In Chung; Simon Weonsang Ro; Yong Han Paik; Jung Il Lee; Man Kil Jung; Min Goo Lee; Young Nyun Park; Kwan Sik Lee; Jung Gyu Park; Hee Dong Park; Kwang-Hyub Han (Apoptosis, 2013)

Dietary aflatoxin B1 intake, genetic polymorphisms of CYP1A2, CYP2E1, EPHX1, GSTM1, and GSTT1, and gastric cancer risk in Korean - Sang-Yong Eom; Dong-Hyuk Yim; Yanwei Zhang; Jung-Kuk Yun; Sun In Moon; Hyo-Yung Yun; Young-Jin Song; Sei-Jin Youn; Taisun Hyun; Joo-Seung Park; Byung Sik Kim; Jong-Young Lee; et al. (Cancer Causes & Control, 2013)

Treadmill exercise represses neuronal cell death and inflammation during Aβ-induced ER stress by regulating unfolded protein response in aged presenilin 2 mutant mice - Eun-Bum Kang; In-Su Kwon; Jung-Hoon Koo; Eung-Joon Kim; Chul-Hyun Kim; Jin Lee; Choon-Ho Yang; Young-Il Lee; In-Ho Cho; Joon-Yong Cho (Apoptosis, 2013)

Genetic differences between wild and hatchery populations of Korean spotted sea bass (Lateolabrax maculatus) inferred from microsatellite markers - Hye Suck An; Jang Wook Lee; Hee Yong Kim; Jong Bin Kim; Dae Soo Chang; Jung Youn Park; Jeong In Myeong; Chul Min An (Genes & Genomics, 2013)

Nicastrin Overexpression in Transgenic Mice Induces Aberrant Behavior and APP Processing - Jun Seo Goo; Yong Bin Kim; Sun Bo Shim; Seung Wan Jee; Su Hae Lee; Ji Een Kim; In Sik Hwang; Young Ju Lee; Moon Hwa Kwak; Chuel Ju Lim; Jin Tae Hong; Dae Youn Hwang (Molecular Neurobiology, 2013)

Neural substrates of acupuncture in the modulation of cravings induced by smoking-related visual cues: an FMRI study - O-Seok Kang; Song-Yi Kim; Geon-Ho Jahng; Hackjin Kim; Jong-Woo Kim; Sun-Yong Chung; Jun-Won Kim; Seung-In Yang; Hi-Joon Park; Hyejung Lee; Younbyoung Chae (Psychopharmacology, 2013)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus - Hae-Mi Nam; Kyung-Sil Chae; Young-Jo Song; Nak-Hyung Lee; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; Sang-Moo Kang; Min-Chul Kim; In-Soo Choi (Archives of Virology, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

Thalassococcus lentus sp. nov., an alphaproteobacterium isolated from seawater of a seaweed farm - Sooyeon Park; Yong-Taek Jung; Soo-In Kim; Jung-Hoon Yoon (Antonie van Leeuwenhoek, 2013)

Effects of Increasing Supplementation of Magnesium in Diets on Productive Performance and Eggshell Quality of Aged Laying Hens - Chan Ho Kim; In Kee Paik; Dong Yong Kil (Biological Trace Element Research, 2013)

Volumetric Analysis of Cerebellum in Short-Track Speed Skating Players - In Sung Park; Nam Joon Lee; Tae-Young Kim; Jin-Hoon Park; Yu-Mi Won; Yong-Ju Jung; Jin-Hwan Yoon; Im Joo Rhyu (The Cerebellum, 2012)

Effect of proton beam irradiation on germination, seedling growth, and pasting properties of starch in rice - Sang-Kuk Kim; Shin-Young Park; Kye-Ryung Kim; Jong-Hee Shin; Su-Yong Kim; Hak-Yoon Kim; In-Jung Lee (Journal of Crop Science and Biotechnology, 2012)

Gene expression profiles of human lung epithelial cells exposed to toluene - Yu-Ri Kim; In-Kyoung Kim; Seung Ho Lee; Eun-Jung Lee; Mi Jung Pyo; Hee Ra Lee; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Toxicology and Environmental Health Sciences, 2012)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

ATM mediates interdependent activation of p53 and ERK through formation of a ternary complex with p-p53 and p-ERK in response to DNA damage - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Minju Kim; Sung Chan Kim; Jae-Bong Park; et al. (Molecular Biology Reports, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Serum Selenium Levels in Korean Hepatoma Patients - In-Wook Kim; Su-Mi Bae; Yong-Wan Kim; Hai-Bo Liu; Si Hyun Bae; Jong Young Choi; Seung Kew Yoon; Pankaj Kumar Chaturvedi; Gantumur Battogtokh; Woong Shick Ahn (Biological Trace Element Research, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Phylogeny and divergence time estimation of Coreoleuciscus splendidus populations (Teleostei: Cypriniformes) endemic to Korea based on complete mitogenome sequences - Keun-Yong Kim; Yoon Kwon Nam; In-Chul Bang (Genes & Genomics, 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Phylogeny and speciation time estimation of two Koreocobitis species (Teleostei; Cypriniformes; Cobitidae) endemic to Korea inferred from their complete mitogenomic sequences - Keun-Yong Kim; In-Chul Bang (Genes & Genomics, 2012)

Stabilization of the As-contaminated soil from the metal mining areas in Korea - Myoung-Soo Ko; Ju-Yong Kim; Sunbeak Bang; Jin-Soo Lee; Ju-In Ko; Kyoung-Woong Kim (Environmental Geochemistry and Health, 2012)

Hepatoprotection of different water extracts from Acer tegmentosum M. on CCl4-induced acute hepatotoxicity in mice: comparative efficacies between the extracts of boughs, twigs, and leaves - Kwang-Yong Shim; Dong-Heui Kim; Soon-Bong Song; Xu-Feng Qi; Yang-Suk Yoon; Hyun-Soo Kim; Jong-In Lee; Hwa-Eun Oh; Soo-Ki Kim; Kyu-Jae Lee (Molecular & Cellular Toxicology, 2011)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Molecular Systematic Study of Chrysosplenium Series Pilosa (Saxifragaceae) in Korea - Yong-In Kim; Young-Dong Kim (Journal of Plant Biology, 2011)

Higher DNA repair activity is related with longer replicative life span in mammalian embryonic fibroblast cells - Seong-Hoon Park; Hong-Jun Kang; Hyun-Seok Kim; Min-Ju Kim; Jee-In Heo; Jeong-Hyeon Kim; Yoon-Jung Kho; Sung Chan Kim; Jaebong Kim; Jae-Bong Park; Jae-Yong Lee (Biogerontology, 2011)

The use of healthy volunteers instead of patients to inform drug dosing studies: a [11C]raclopride PET study - Euitae Kim; Oliver D. Howes; Bo-Hyung Kim; Kyung-Sang Yu; Jae Min Jeong; Jae Sung Lee; Su Jin Kim; In-Jin Jang; Jung Shin Park; Yong Gil Kim; Sang-Goo Shin; Federico E. Turkheimer; et al. (Psychopharmacology, 2011)

Expression of the protective antigen for PEDV in transgenic duckweed, Lemna minor - Suk-Min Ko; Hyeon-Jin Sun; Myung Jin Oh; In-Ja Song; Min-Jae Kim; Hyun-Sook Sin; Chang-Hyo Goh; Yong-Woo Kim; Pyung-Ok Lim; Hyo-Yeon Lee; Suk Weon Kim (Horticulture, Environment, and Biotechnology, 2011)

Expression of a recombinant chimeric protein of hepatitis A virus VP1-Fc using a replicating vector based on Beet curly top virus in tobacco leaves and its immunogenicity in mice - Ho Yong Chung; Hyun Ho Lee; Kyung Il Kim; Ha Young Chung; Jeon Hwang-Bo; Jong Hwa Park; Garry Sunter; Jong Bum Kim; Dong Hwa Shon; Wonyong Kim; In Sik Chung (Plant Cell Reports, 2011)

Natural 15N abundance of paddy rice (Oryza sativa L.) grown with synthetic fertilizer, livestock manure compost, and hairy vetch - Soek-In Yun; Sang-Sun Lim; Gwang-Sung Lee; Sang-Mo Lee; Han-Yong Kim; Hee-Myong Ro; Woo-Jung Choi (Biology and Fertility of Soils, 2011)

Isolation and characterization of 28 polymorphic SSR loci from castor bean (Ricinus communis L.) - Kyoung-In Seo; Gi-An Lee; Kyung-Ho Ma; Do-Yoon Hyun; Yong-Jin Park; Jong-Wook Jung; Sok-Young Lee; Jae-Gyun Gwag; Chung-Kon Kim; Myung-Chul Lee (Journal of Crop Science and Biotechnology, 2011)

Importance of region-specific epithelial rearrangements in mouse rugae development - Wern-Joo Sohn; Hitoshi Yamamoto; Hong-In Shin; Zae Young Ryoo; Sanggyu Lee; Yong-Chul Bae; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

ERK mediates anti-apoptotic effect through phosphorylation and cytoplasmic localization of p21Waf1/Cip1/Sdi in response to DNA damage in normal human embryonic fibroblast (HEF) cells - Jee-In Heo; Soo-Jin Oh; Yoon-Jung Kho; Jeong-Hyeon Kim; Hong-Joon Kang; Seong-Hoon Park; Hyun-Seok Kim; Jong-Yeon Shin; Min-Ju Kim; Sung Chan Kim; Jae-Bong Park; Jaebong Kim; et al. (Molecular Biology Reports, 2011)

Suppression of NH3 and N2O emissions by massive urea intercalation in montmorillonite - Kwang Seop Kim; Man Park; Choong Lyeal Choi; Dong Hoon Lee; Young Jin Seo; Chan Yong Kim; Jong Su Kim; Seok-In Yun; Hee-Myong Ro; Sridhar Komarneni (Journal of Soils and Sediments, 2011)

Autoinduction of a genetic locus encoding putative acyltransferase in Corynebacterium glutamicum - Hee-Sung Shin; Yong-Jae Kim; In-Hwa Yoo; Heung-Shick Lee; Shouguang Jin; Un-Hwan Ha (Biotechnology Letters, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Environmental quality of Korean coasts as determined by modified Shannon–Wiener evenness proportion - Jae-Won Yoo; Yong-Woo Lee; Jennifer L. Ruesink; Chang-Gun Lee; Chang-Soo Kim; Mi-Ra Park; Kon-Tak Yoon; In-Seo Hwang; Jun-Ho Maeng; Rutger Rosenberg; Jae-Sang Hong (Environmental Monitoring and Assessment, 2010)

Correlation between nutrition intake and gene expression profiles in children with asthma - Jae-Eun Pie; Yu-Ri Kim; In-Kyoung Kim; Sang-Hui Seo; Seung Ho Lee; Hee Ra Lee; Young Yoo; Ji Tae Chung; Jong Pil Youn; MoonJu Oh; Seung Yong Hwang; Meyoung-Kon Kim (Molecular & Cellular Toxicology, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Arabidopsis thaliana Rubisco small subunit transit peptide increases the accumulation of Thermotoga maritima endoglucanase Cel5A in chloroplasts of transgenic tobacco plants - Suyeon Kim; Dae-Seok Lee; In Seong Choi; Sung-Ju Ahn; Yong-Hwan Kim; Hyeun-Jong Bae (Transgenic Research, 2010)

Variation in the phenotypic features and transcripts of color mutants of chrysanthemum (Dendranthema grandiflorum) derived from gamma ray mutagenesis - Geung-Joo Lee; Sung Jin Chung; In Sook Park; Jong Suk Lee; Jin-Baek Kim; Dong Sub Kim; Si-Yong Kang (Journal of Plant Biology, 2008)

Artificial neural networks for predicting DGPS carrier phase and pseudorange correction - Arif Indriyatmoko; Taesam Kang; Young Jae Lee; Gyu-In Jee; Yong Beom Cho; Jeongrae Kim (GPS Solutions, 2008)

Somatic embryogenesis and plant regeneration from immature seeds of Magnolia obovata Thunberg - Yong Wook Kim; So Young Park; In Sun Park; Heung Kyu Moon (Plant Biotechnology Reports, 2007)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Isolation and structural analysis of bamylocin A, novel lipopeptide from Bacillus amyloliquefaciens LP03 having antagonistic and crude oil-emulsifying activity - Sang-Cheol Lee; Sun-Hee Kim; In-Hye Park; Soo-Yeol Chung; Yong-Lark Choi (Archives of Microbiology, 2007)

Influence of accumulated leachate on settlement and in-situ geotechnical properties of a landfill site - Yeon-Soo Jang; Yong-In Kim (Geosciences Journal, 2007)

Hypoxia-induced cell death of HepG2 cells involves a necrotic cell death mediated by calpain - Min-Ju Kim; Soo-Jin Oh; Seong-Hoon Park; Hong-Jun Kang; Moo-Ho Won; Tae-Cheon Kang; In Koo Hwang; Jae-Bong Park; Jong-Il Kim; Jaebong Kim; Jae-Yong Lee (Apoptosis, 2007)

ENA Actimineral Resource A restores bone loss and bone quality in ovariectomized rats - Sun Hee Do; Sung-Yong Hwa; Won-Il Jeong; Ji-Won Lee; Hyun-Jung Kim; In-Seon Lee; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2007)

Reproducibility of Quantitative Estimate of Magnetocardiographic Ventricular Depolarization and Repolarization Parameters in Healthy Subjects and Patients with Coronary Artery Disease - Hyun Kyoon Lim; Namsik Chung; Kiwoong Kim; Young-Guk Ko; Hyukchan Kwon; Yong-Ho Lee; Jin-Bae Kim; Jung Rae Cho; Jin-Mok Kim; In-Seon Kim; Yong Ki Park (Annals of Biomedical Engineering, 2006)

Recombinant expression of human cathelicidin (hCAP18/LL-37) in Pichia pastoris - In-Pyo Hong; Sung-Jae Lee; Yong-Seok Kim; Shin-Geon Choi (Biotechnology Letters, 2006)

Characterization of copper, zinc superoxide dismutase from a cartilaginous shark species, Scyliorhinus torazame (Carcharhiniformes) - Yoon Kwon Nam; Young Sun Cho; Keun-Yong Kim; In Chul Bang; Ki Hong Kim; Sung Koo Kim; Dong Soo Kim (Fish Physiology and Biochemistry, 2006)

Optimization of direct somatic embryogenesis from mature zygotic embryos ofPanax ginseng C. A. Meyer - Ok Tae Kim; Tae Soo Kim; Dong Soo In; Kyong Hwan Bang; Young Chang Kim; Yong Eui Choi; Seon Woo Cha; Nak Sul Seong (Journal of Plant Biology, 2006)

Temperature-dependent index of mitotic interval τ0 in greenling Hexagrammos otakii - In-Seok PARK; Eun-Mi KIM; Seon Rang WOO; Sung-Yong OH; Dong Soo KIM; Jun Wook HUR (Fisheries Science, 2006)

Lidocaine hydrochloride-sodium bicarbonate as an anesthetic for soft-shelled turtle Pelodiscus sinensis - In-Seok PARK; Sung Hwoan CHO; Jun Wook HUR; Gyeng-Cheol CHOI; Sung-Yong OH; Dong Soo KIM; Jae-Seong LEE (Fisheries Science, 2006)

Expression of recombinant endostatin in Agrobacterium-inoculated leaf-disks of Nicotiana tabacum var. xanthi - Seong Hyun Hong; Kyung Il Kim; Ho Yong Chung; You Jung Kim; Garry Sunter; David M. Bisaro; In Sik Chung (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Transforming Growth Factor (TGF)-β1 Releasing Tricalcium Phosphate/Chitosan Microgranules as Bone Substitutes - Jue-Yeon Lee; Yang-Jo Seol; Kyoung-Hwa Kim; Yong-Moo Lee; Yoon-Jeong Park; In-Chul Rhyu; Chong-Pyoung Chung; Seung-Jin Lee (Pharmaceutical Research, 2004)

Expression of recombinant endostatin in Agrobacterium-inoculated leaf disks of Nicotiana tabacum var. Xanthi - Seong Hyun Hong; Kyung Il Kim; Ho Yong Chung; You Jung Kim; Garry Sunter; David M. Bisaro; In Sik Chung (Biotechnology Letters, 2004)

Single nucleotide polymorphism discovery and linkage mapping of lipoxygenase-2 gene (Lx 2) in soybean - Moon Young Kim; Bo-Keun Ha; Tae-Hwan Jun; Eun-Young Hwang; Kyujung Van; Yong In Kuk; Suk-Ha Lee (Euphytica, 2004)

Subcellular accumulation of Cu in the Antarctic bivalve Laternula elliptica from a naturally Cu-elevated bay of King George Island - Heeseon J. Choi; In-Young Ahn; Ko-Woon Kim; Yong-Suk Lee; In-Sook Lee; Kye-Heon Jeong (Polar Biology, 2003)

Co-expression of a Modified Maize Ribosome-inactivating Protein and a Rice Basic Chitinase Gene in Transgenic Rice Plants Confers Enhanced Resistance to Sheath Blight - Ju-Kon Kim; In-Cheol Jang; Ray Wu; Wei-Neng Zuo; Rebecca S. Boston; Yong-Hwan Lee; Il-Pyung Ahn; Baek Hie Nahm (Transgenic Research, 2003)

Comparison of 16S rDNA analysis and rep-PCR genomic fingerprinting for molecular identification of Yersinia pseudotuberculosis - Wonyong Kim; Mi-Ok Song; Wonkeun Song; Ki-Jung Kim; Sang-In Chung; Chul-Soon Choi; Yong-Ha Park (Antonie van Leeuwenhoek, 2003)

Expression of Interferon Inducible Genes Following Hantaan Virus Infection as a Mechanism of Resistance in A549 Cells - Jae-Hwan Nam; Kyung-A Hwang; Cheong-Hee Yu; Tae-Hoon Kang; Jae-Young Shin; Woo-Young Choi; In-Beom Kim; Young-Ran Joo; Hae-Wol Cho; Keun-Yong Park (Virus Genes, 2003)

Design and biological activity of synthetic oligopeptides with Pro-His-Ser-Arg-Asn (PHSRN) and Arg-Gly-Asp (RGD) motifs for human osteoblast-like cell (MG-63) adhesion - Tae-Il Kim; Jun-Hyeog Jang; Yong-Moo Lee; In-Cheol Ryu; Chong-Pyoung Chung; Soo-Boo Han; Sang-Mook Choi; Young Ku (Biotechnology Letters, 2002)

Decolorization of triphenylmethane and azo dyes by Citrobacter sp. - Sun-Young An; Sang-Ki Min; In-Ho Cha; Yong-Lark Choi; Young-Su Cho; Cherol-Ho Kim; Young-Choon Lee (Biotechnology Letters, 2002)

Environmental fate of the triazole fungicide propiconazole in a rice-paddy-soil lysimeter - In Seon Kim; Lee A. Beaudette; Jae Han Shim; Jack T Trevors; Yong Tack Suh (Plant and Soil, 2002)

Expression and purification of Listeria innocua Sv6b p60 invasion associated protein - Yong-Hee Choi; Sang-Hoon Han; Yong-Soon Lee; Yoon-Kyu Lim; In-Gyu Kim; Byoung-Su Yoon (Biotechnology Letters, 2001)

Purification and biochemical characterization of a fibrinolytic enzyme from Bacillus subtilis BK-17 - Yong Kee Jeong; Jeong Uck Park; Hyun Baek; Sung Hoon Park; In Soo Kong; Dong Wan Kim; Woo Hong Joo (World Journal of Microbiology and Biotechnology, 2001)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

Production of recombinant rotavirus VP6 from a suspension culture of transgenic tomato (Lycopersicon esculentum Mill.) cells - In Sik Chung; Chang Heon Kim; Kyung Il Kim; Seong Hyun Hong; Jong Hwa Park; Ju Kon Kim; Won Yong Kim (Biotechnology Letters, 2000)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)

Double-labeling techniques demonstrate that rod bipolar cells are under GABAergic control in the inner plexiform layer of the rat retina - In-Beom Kim; Mun-Yong Lee; S.-J. Oh; Keun-Young Kim; M.-H. Chun (Cell and Tissue Research, 1998)